A Revised Preparation of (4-Acetamido-2,2,6,6-tetramethylpiperidin-1-yl)oxyl and 4-Acetamido-2,2,6,6-tetramethyl-1-oxopiperidinium Tetrafluoroborate: Reagents for Stoichiometric Oxidations of Alcohols - J. Tilley, Leon; Bobbitt, James M.; Murray, Stephanie A.; Camire, Casey E.; Eddy, Nicholas A. (Synthesis, 2013)
Revised preparations of (4-acetamido-2,2,6,6-tetramethylpiperidin-1-yl)oxyl and the corresponding oxoammonium salt, 4-acetamido-2,2,6,6-tetramethyl-1-oxoammonium tetrafluoroborate are presented together with some of the important properties of these two oxidizing reagents.
Keywords: oxidations; catalysis; green chemistry; alcohols; aldehydes; ketones